Work-Life Balance Among Informal Sector Workers: A Systematic Review of Challenges and Strategies - Afiani, Alvira Choirina (Perhimpunan Dokter Kedokteran Komunitas dan Kesehatan Masyarakat Indonesia (PDK3MI), 2025)
Informal work is a work arrangement that, in practice, does not comply with national labor laws, leaving its workers uncertain about their legal protection, facing challenges in maintaining a consistent work schedule, and struggling to balance their work and family life. The characteristics of the informal sector, such as low and unstable wages, can also cause stress and anxiety, which in turn disrupts work-life balance or WLB. WLB can be defined as the lack of conflict or interference between work and family roles. Understanding the details about WLB on informal sector workers. A search for articles through Google Scholar yielded 12 articles related to WLB among informal workers, including online drivers, bus drivers, tailors, and farmers. The Study revealed that informal workers often face challenges in the form of long and irregular working hours, low and unstable wages, and limited legal and social protection. WLB of informal workers can be influenced by working hours, wages, health and safety of work environment, training provision or requirements, social integration, individual factors, economic and family factors, influence of technology, loyalty and attitude factors, also salary factors. In addition, there are natural conditions and job insecurity that influence WLB in the agricultural sector. Poor WLB can result in high levels of stress, decreased productivity, and increased health risks. WLB among informal workers can be caused by many factors, so more effective policy interventions are needed from the government, such as improving regulations and strengthening Pos UKK.